Kajian Bagaimana Keberadaan Pasar Kontenporer Mempengaruhi Pedagang Konvenssional di Kota Gumawang - Ginanjar Wahyudi; Turmudzi Basyir; Siti Afifah (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This study explores the influence of the presence of contemporary markets on traditional market traders in Gumawang City. Globalization and technological advancements have transformed the needs and lifestyles of society, prompting the emergence of various types of markets. Modern markets, with more organized management and better facilities, often attract consumer attention away from traditional markets, despite offering higher prices. This research employs a qualitative method with an interactive approach, where the researcher directly interacts with the subjects of the study. The findings indicate that 75% of traditional market traders do not feel threatened by modern markets, as they can still attract customers with lower prices and negotiation flexibility. However, 25% of traders experience negative impacts due to decreased income, with an average decline ranging from 10% to 15%. This study highlights the necessity for traditional market traders to adapt to changes and seek new strategies to sustain their businesses amidst increasing competition. The findings aim to provide a deeper understanding of market dynamics in Gumawang City and support the development of better policies for traditional markets.